Hubungan Makroekonomi terhadap Kinerja Keuangan pada Bank Konvensional dan Bank Syariah di Jawa Timur - Sishadiyati -; Chantya Anggi Kirana (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
Macroeconomic factors can be said to have a relationship with the financial performance of banks, both conventional banks and Islamic banks. The condition of the banking sector in East Java is very vulnerable to economic shocks that occur. So it requires a very independent and good liquidity management. The existing banking sector is still very dependent on the policies made by the central bank and the government. Then if there is a financial difficulty caused by unfavorable macroeconomic conditions, then the bank's financial performance may also be disrupted. Based on the analysis of data that has been explained that macroeconomic factors such as GRDP, inflation rate, unemployment rate, BI Rate and exchange rate, which have a very large relationship to the performance of conventional banks and Islamic banks in East Java is the BI rate. This shows that the banking sector in East Java must pay special attention to the dynamics of macroeconomic factors that occur. Whereas the financial performance between Islamic banks and conventional banks shows a difference. This is because the management of bank financial performance between Islamic banks and conventional banks has a different policy.